Translation Problems of YouTube Auto Translation of Johnny Harris' "Why Indonesia is always Erupting" - Thomas Aquino Amadeus Sindhunata; Priska Meilasari (Humaniora Scientia, 2024)
The advance of technology has eased human’s work in almost all field of jobs including in the field of translation. The traditional translator fully used their translation skills in transfering the messages of original language to the targeted language. Nowadays, by the existence of translation technology, translator could pose as a reviewer oft he translation product done by the translation machine. One of the media which serves automated translation is YouTube. YouTube auto translation is analyzed in this research by looking at the probloms which might occur when audience accessed it. This is a qualitative research which try to explain the nature oft he data descriptively. The data are taken from Johnny Harris‘ YouTube video „Why Indonesia is always Erupting“. Thirtheen data of possible problems occur in YouTube auto translation are explained in result and discussion section oft he paper.